The pseudokinase TRIB3 controls adipocyte lipid homeostasis and proliferation in vitro and in vivo - Miguel Hernández-Quiles; Laura Martinez Campesino; Imogen Morris; Zabran Ilyas; Steve Reynolds; Nguan Soon Tan; Paula Sobrevals Alcaraz; Edwin C.A. Stigter; Ákos Varga; János Varga; Robert van Es; Harmjan Vos; et al. (Elsevier, 2023)
Objective: In vivo studies in humans and mice have implicated the pseudokinase Tribbles 3 (TRIB3) in various aspects of energy metabolism. Whilst cell-based studies indicate a role for TRIB3 in adipocyte differentiation and function, it is unclear if and how these cellular functions may contribute to overall metabolic health. Methods: We investigated the metabolic phenotype of whole-body Trib3 knockout (Trib3KO) mice, focusing on adipocyte and adipose tissue functions. In addition, we combined lipidomics, transcriptomics, interactomics and phosphoproteomics analyses to elucidate cell-intrinsic functions of TRIB3 in pre- and mature adipocytes. Results: Trib3KO mice display increased adiposity, but their insulin sensitivity remains unaltered. Trib3KO adipocytes are smaller and display higher Proliferating Cell Nuclear Antigen (PCNA) levels, indicating potential alterations in either i) proliferation-differentiation balance, ii) impaired expansion after cell division, or iii) an altered balance between lipid storage and release, or a combination thereof. Lipidome analyses suggest TRIB3 involvement in the latter two processes, as triglyceride storage is reduced and membrane composition, which can restrain cellular expansion, is altered. Integrated interactome, phosphoproteome and transcriptome analyses support a role for TRIB3 in all three cellular processes through multiple cellular pathways, including Mitogen Activated Protein Kinase- (MAPK/ERK), Protein Kinase A (PKA)-mediated signaling and Transcription Factor 7 like 2 (TCF7L2) and Beta Catenin-mediated gene expression. Conclusions: Our findings support TRIB3 playing multiple distinct regulatory roles in the cytoplasm, nucleus and mitochondria, ultimately controlling adipose tissue homeostasis, rather than affecting a single cellular pathway.